2016
DOI: 10.1530/erp-16-0028
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis for the echocardiographic assessment of right ventricular structure and function in ARVC: a Study by the Research and Audit Committee of the British Society of Echocardiography

Abstract: IntroductionArrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited pathology that can increase the risk of sudden death. Current task force criteria for echocardiographic diagnosis do not include new, regional assessment tools which may be relevant in a phenotypically diverse disease. We adopted a systematic review and meta-analysis approach to highlight echocardiographic indices that differentiated ARVC patients and healthy controls.MethodsData was extracted and analysed from prospective trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…35 The current study reports no difference in TAPSE, RVFAC, or standard indices of TDI between RFL athletes and controls, and therefore, the presence of abnormal values should prompt further investigation. 35 The current study reports no difference in TAPSE, RVFAC, or standard indices of TDI between RFL athletes and controls, and therefore, the presence of abnormal values should prompt further investigation.…”
Section: Rv Functionmentioning
confidence: 54%
See 1 more Smart Citation
“…35 The current study reports no difference in TAPSE, RVFAC, or standard indices of TDI between RFL athletes and controls, and therefore, the presence of abnormal values should prompt further investigation. 35 The current study reports no difference in TAPSE, RVFAC, or standard indices of TDI between RFL athletes and controls, and therefore, the presence of abnormal values should prompt further investigation.…”
Section: Rv Functionmentioning
confidence: 54%
“…10 It is considered best practice to apply a multifactorial approach to functional assessment including the use of TAPSE, RVFAC, and RV TDI. 35 The current study reports no difference in TAPSE, RVFAC, or standard indices of TDI between RFL athletes and controls, and therefore, the presence of abnormal values should prompt further investigation.…”
Section: Rv Functionmentioning
confidence: 54%
“…Both Yoerger et al [57] and Vitarelli et al [55] reported that RV strain has the highest sensitivity and specificity for the diagnosis of ARVC. There were no ARVC patients demonstrating a peak RV strain above − 21 %; that is, much lower than the currently accepted normal RV strain of − 28 % [45] (▶Fig. 1).…”
Section: New Echocardiographic Parametersmentioning
confidence: 66%
“…Compared to the LV, there are limited RV STE studies in athletes and there is a lack of universally accepted cut-off values [ 25 ••]. A recent and large meta-analysis of RV structure and function in ARVC [ 67 ] concluded that RV ɛ is significantly lower in ARVC patients compared to controls with a range of RV ɛ in controls of − 27 to − 31% and in ARVC patients of − 13 to − 21%. A cut-off for pathology of less than − 21% was therefore suggested.…”
Section: Speckle Tracking Echocardiography and The Ahmentioning
confidence: 99%